2002
DOI: 10.1074/jbc.m205018200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Properties of the Procollagen C-proteinase Enhancer Protein Shed Light on the Mechanism of Stimulation of BMP-1

Abstract: Procollagen C-proteinase enhancer (PCPE) is an extracellular matrix glycoprotein that binds to the C-propeptide of procollagen I and can enhance the activities of procollagen C-proteinases up to 20-fold. To determine the molecular mechanism of PCPE activity, the interactions of the recombinant protein with the procollagen molecule as well as with its isolated C-propeptide domain were studied using surface plasmon resonance (BIAcore) technology. Binding required the presence of divalent metal cations such as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 57 publications
5
70
1
Order By: Relevance
“…3, A and B). Because PCPE binds to procollagen C-propeptide via its N-terminal CUB domain (36) the iTRAQ ratios and peptide mapping are consistent with the shedding of the C-terminal netrin domain of PCPE upon proteolysis with the N-terminal CUB domain remaining bound to the procollagen. We confirmed this using C-terminal FLAGtagged PCPE in culture medium that was cleaved by MMP-2 to release a 22-kDa C-terminal FLAG-tagged fragment encompassing the netrin domain (Fig.…”
Section: Table I Comparison Of the Number Of Proteins Identified By Omentioning
confidence: 80%
See 1 more Smart Citation
“…3, A and B). Because PCPE binds to procollagen C-propeptide via its N-terminal CUB domain (36) the iTRAQ ratios and peptide mapping are consistent with the shedding of the C-terminal netrin domain of PCPE upon proteolysis with the N-terminal CUB domain remaining bound to the procollagen. We confirmed this using C-terminal FLAGtagged PCPE in culture medium that was cleaved by MMP-2 to release a 22-kDa C-terminal FLAG-tagged fragment encompassing the netrin domain (Fig.…”
Section: Table I Comparison Of the Number Of Proteins Identified By Omentioning
confidence: 80%
“…PCPE stimulates procollagen processing, thereby triggering assembly of collagen fibrils (36). Interestingly the C-terminal netrin domain of PCPE is a weak inhibitor of MMP-2 (41) that might homeostatically regulate the levels of PCPE.…”
Section: Discussionmentioning
confidence: 99%
“…5, the binding of PCPE-1 to the immobilized miniprocollagen III was initially fast and then slowed down without reaching a plateau, even when the injection time was doubled. This sensorgram is reminiscent of the sensorgrams previously obtained when the C-propeptides of procollagen I or III were injected over immobilized PCPE-1 (35). The various PCPE-1 mutants were then sequentially injected over the same regenerated mini-procollagen III surface at a fixed concentration of 100 nM, in the absence or presence of 5 mM Ca 2ϩ (Fig.…”
Section: Identification Of Targetmentioning
confidence: 99%
“…We have already shown that the C-propeptide of procollagen III binds calcium (35) and thus, mini-procollagen III like PCPE-1 is expected to bind calcium. To explore further the role played by calcium in PCPE-1, we monitored the effect of calcium binding on the intrinsic fluorescence of PCPE-1.…”
Section: Identification Of Targetmentioning
confidence: 99%
See 1 more Smart Citation